Eur J Biol 2020
DOI: 10.26650/eurjbiol.2020.0077
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Cytotoxic, and Enzyme Inhibitory Activities of Agropyron repens and Crataegus monogyna Species

Abstract: The aim of this study was to investigate antioxidant, enzyme inhibitory and cytotoxic activities of Agropyron repens and Crataegus monogyna methanol extracts with total phenolic and flavonoid contents.Materials and Methods: Total phenolic and flavonoid contents of A. repens and C. monogyna methanol extracts were measured according to Folin Ciocalteu and aluminum nitrate methods, respectively. Antioxidant and enzyme inhibitory activities of the methanol extracts were tested spectrophotometrically. Also, cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…These properties have appeared to be linked to the presence of phytochemicals generally maintaining the appropriate cell redox balance through diverse mechanisms, including antioxidant activity [ 27 ]. Studies on the genus have shown that phytochemicals such as oligomeric procyanidins, flavonoids, triterpenes, polysaccharides, catecholamines and many of these compounds have been evaluated for biological functions [ 20 , 58 , 59 , 60 ]. In this context, several studies have revealed that the C. monogyna fruit represents a great source and one of the highest in terms of phenolic content with a value up to 30.63 mg gallic acid equivalent (GAE) g −1 in fully ripe fruit [ 61 ].…”
Section: Antioxidant Properties Of Hawthorn Extractsmentioning
confidence: 99%
“…These properties have appeared to be linked to the presence of phytochemicals generally maintaining the appropriate cell redox balance through diverse mechanisms, including antioxidant activity [ 27 ]. Studies on the genus have shown that phytochemicals such as oligomeric procyanidins, flavonoids, triterpenes, polysaccharides, catecholamines and many of these compounds have been evaluated for biological functions [ 20 , 58 , 59 , 60 ]. In this context, several studies have revealed that the C. monogyna fruit represents a great source and one of the highest in terms of phenolic content with a value up to 30.63 mg gallic acid equivalent (GAE) g −1 in fully ripe fruit [ 61 ].…”
Section: Antioxidant Properties Of Hawthorn Extractsmentioning
confidence: 99%